Implementasi Program Nagari Swakelola Jaminan Kesehatan Nasioal (SWA-JKN) di Nagari Taram Kabupaten Lima Puluh Kota - Nindy Zettira; Hasbullah Malau (PUBLICNESS: Journal of Public Administration studies, 2022)
Nagari Taram Regulation Number 9 of 2019 concerning Taram Community Health Insurance is a reference in the implementation of the Nagari Swa-JKN Program. This program is given to poor independent communities (PBPU). In its implementation, the Nagari Swa-JKN Program has not been running effectively. This study aims to find the inhibiting factors in the implementation of the Nagari Swa-JKN Program. This study uses a qualitative descriptive research method. This research was conducted in Nagari Taram, Harau District, Lima Puluh Kota Regency. The results of this study indicate that the inhibiting factors in the implementation of the Nagari Swa-JKN Program, Harau District, Lima Puluh Kota Regency, namely (a) human resources of Pelita volunteers who are not qualified (b) no funding sources for Pelita volunteers (c) no supporting infrastructure for Pelita volunteers, (d) the low level of education and public understanding of health insurance, and (e) the decline in community economic activities due to the COVID-19 pandemic.